Evaluation of a curcumin-containing mucoadhesive film for periodontal postsurgical pain control - Anu Anil; Sheela Kumar Gujjari; Madhugiri Prakash Venkatesh (Wolters Kluwer Medknow Publications, 2019)
Background: Management of pain and discomfort is important to make the postoperative period as pleasant as possible. Nonsteroidal anti-inflammatory drugs are traditionally prescribed; however, they are associated with numerous side effects. As a result, nutraceuticals such as curcumin are widely used for its well-known safety and medicinal values. Hence, the aim of this study is to evaluate the efficacy of a curcumin mucoadhesive film for postsurgical pain control. Materials and Methods: This was a split-mouth study, consisting of 15 systemically healthy patients with 30 sites, who were randomly allocated into test (curcumin mucoadhesive film) and control (placebo mucoadhesive film) groups using coin toss method. A questionnaire was given to patients to evaluate the postoperative pain and swelling and the number of rescue medications taken. Statistical analyses used were Friedman test, Wilcoxon signed-rank test, and McNemar's test. Results: No adverse effects were reported and healing was uneventful in all patients. The Numerical rating scale pain score showed significantly lesser pain at 1, 2, 3, 4, 5, and 24 h in the test group. Significantly more number of analgesics was consumed in total in the control group than that in the test group. Conclusion: Within the limitations of this study, it may be concluded that curcumin mucoadhesive film showed promising results in reducing postoperative pain and swelling over a period of 1 week, hence showing its analgesic effect after periodontal surgeries.